2013
DOI: 10.1002/pc.22518
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-static and dynamic experiment investigations on the crashworthiness response of composite tubes

Abstract: Crashworthiness performance of carbon and glass composite tubes have been comprehensive investigated under quasi‐static and dynamic axial crush testing. In this study, collapse modes and specific energy absorption (SEA) of different ply orientation of carbon fabric composites and unidirectional glass tubes were analyzed. For the weaker tensile strength and bending strength of glass composites, crack propagated approximately perpendicular to the fiber direction when the ply angle was small. Large amount of fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Results indicate that CF/Nylon 6 laminates exhibited higher fracture toughness than CF/Epoxy laminates, which indicates the capability of UD CF/Nylon 6 composites containing a crack to resist fracture was better than CF/Epoxy composites [40].…”
Section: Fracture Toughness Of 90 Degree Ud Laminatesmentioning
confidence: 96%
“…Results indicate that CF/Nylon 6 laminates exhibited higher fracture toughness than CF/Epoxy laminates, which indicates the capability of UD CF/Nylon 6 composites containing a crack to resist fracture was better than CF/Epoxy composites [40].…”
Section: Fracture Toughness Of 90 Degree Ud Laminatesmentioning
confidence: 96%
“…Various crush speeds were adapted in the literature. According to Ma and Yan, 63 Hu et al, 64 Attia et al, 1 Lykakos et al, 65 and Morales et al, 66 the crosshead speed was set to 10 mm/ min.…”
Section: Uniaxial Quasi-static Compression Testmentioning
confidence: 99%
“…Several studies have reported on the energy absorption capacity of crashworthy structures under quasi‐static [ 4–7 ] and dynamic impact loads. [ 6,8,9 ] Dynamic impact can be divided into low speed, [ 10 ] high‐speed, [ 11 ] and ballistic impact.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of these advantages, there is a growing demand for new high-performance materials with high strength, high modulus, low weight, and good toughness properties. [1] Several studies have reported on the energy absorption capacity of crashworthy structures under quasistatic [4][5][6][7] and dynamic impact loads. [6,8,9] Dynamic impact can be divided into low speed, [10] high-speed, [11] and ballistic impact.…”
Section: Introductionmentioning
confidence: 99%